Training Needs of Portuguese Practitioners Working with Children and Young People with Complex and Intense Support Needs - Candeias, Adelinda (2018)
Upon the publication in Portugal of Decree-Law No. 3/2008, inclusive education for all children in regular schools became compulsory. In a short period of time, the educational community (special education teachers, regular education teachers, administrators, and technicians) were required to include and teach all students in regular schools. This article characterizes Portuguese teachers’ perceptions (TPs; N ¼ 105) about the training needs of practitioners working with children and young people with complex and intense support needs (CISNs). In this work, we use data collected using the questionnaire for practitioners working with children and young people with CISN—TPs, which was drawn up under the auspices of project ENABLINþ. The results of content analysis showed that the most frequently mentioned themes were special education, intervention strategies, international classification of functioning, disability and health, educational legislation, and family everyone (practitioners and nonpractitioners), and should aim to improve practices, while being sufficiently flexible and differentiated to meaningfully inform each professional